Spin-Orbit Coupled s-Wave Superconductor in One-Dimensional Optical Lattice*Supported by National Program for Basic Research of MOST (973 grant), and by National Natural Science Foundation of China under Grant Nos. 11121063, 11174360, 11374354, 11274195, 2011CB606405 and 2013CB922000. (1st April 2015) - Yang, Li-Jun; Lang, Li-Jun; Lü, Rong; Hu, Hai-Ping
Abstract We study the topological properties of spin-orbit coupled s-wave superconductor in one-dimensional optical lattice. Compared to its corresponding continuum model, the single particle spectrum is modified by the optical lattice and the topological phase which is characterized by the Majorana edge modes can survive in two regions of the single-particle spectrum. With the help of the self-consistent Bogoliubov-de Gennes calculation in the harmonic trap, we find that the existence of an upper critical magnetic field removes the topological superconductor phase to the trap wings. We also study the effects of nonmagnetic and magnetic impurity on the topological properties, and find the universal behavior of the mid-gap state induced by impurity in the topological superconductor phase in strong scattering limit.